2019
DOI: 10.1007/s00268-019-05312-4
|View full text |Cite
|
Sign up to set email alerts
|

Invasiveness and Metastatic Aggressiveness in Small Differentiated Thyroid Cancers: Demography of Small Papillary Thyroid Carcinomas in the Swedish Population

Abstract: Background The western world is seeing a rising incidence of thyroid cancer. Improved diagnostic methods do not entirely explain this increase. Papillary thyroid carcinoma (PTC) is the most common subtype of thyroid cancer. Small PTC (B20 mm) and especially papillary thyroid microcarcinomas (PTMC B10 mm) are considered to be lowrisk tumors but some cases are considerably more aggressive. Sufficient understanding of these mechanisms is a long-term goal for more efficient and safer treatment of these tumors. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…The results support the hypothesis that recurrence rate, rather than mortality rate, is a preferable clinical measure when discussing sPTC. Given the difference regarding intervention-requiring cancer recurrence between N1b and N1a/N0, LN status plays an important role in individual risk stratification, and this emphasizes the need for thorough preoperative LN mapping even in sPTC [ 8 ]. Central lymph node metastasis (CLNM) has been shown to be the strongest risk factor for lateral lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results support the hypothesis that recurrence rate, rather than mortality rate, is a preferable clinical measure when discussing sPTC. Given the difference regarding intervention-requiring cancer recurrence between N1b and N1a/N0, LN status plays an important role in individual risk stratification, and this emphasizes the need for thorough preoperative LN mapping even in sPTC [ 8 ]. Central lymph node metastasis (CLNM) has been shown to be the strongest risk factor for lateral lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the good prognosis, the general approach is towards less aggressive management of these small tumours [ 4 ]. Although most sPTCs are considered low risk cancers, some are considerably more aggressive than others with a high recurrence risk [ 2 , 5 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unexplained regional differences in the distribution and increase of sPTC have been listed in Sweden (32). Early detection of more aggressive forms of thyroid cancer is essential for proper surgical and oncological treatment of these patients.…”
Section: Introductionmentioning
confidence: 99%
“…This method is innovative and could draw attention to as yet unknown factors influencing thyroid cancer, and may potentially prove useful within other fields of medical research. Unexplained regional differences in the distribution and increase of sPTC have been listed in Sweden (32). Early detection of more aggressive forms of thyroid cancer is essential for proper surgical and oncological treatment of these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Nearly 50% of thyroid cancer cases consist of PTC measuring 10 mm or less in size (papillary thyroid microcarcinoma [PTMC]) (2) . It has been reported that although the clinical outcome of patients with PTMC (usually considered to be an indolent tumor) is excellent, there are still a considerable number of cases related to poor prognoses, such as capsule invasion (3)(4)(5) . Based on the excellent prognosis of patients with PTMC, Kuma Hospital and Cancer Institute Hospital of the Japanese Foundation for Cancer Research first proposed the concept of indolent PTMC (cancer foci without lymph node metastasis, extrathyroidal extension [ETE], or distant metastasis) and aggressive PTMC (cancer foci with lymph node metastasis, ETE, or distant metastasis) and began a study of active surveillance for indolent PTMC instead of surgical treatment (6) .…”
Section: Introductionmentioning
confidence: 99%